Telepon Selular, Partisipasi dan Kebijakan: Analisis Persepsi Masyarakat Kota Pangkalpinang tentang Pemanfaatan SMS untuk Menyerap Aspirasi Masyarakat - Ramdhani Harahap, Fitri (SOSIOLOGI, 2009)
Community to provide a high appreciation of the presence of the SMS which is used as a medium for channeling aspirations. Aspirations of the community through the delivery of SMS is one way of effective, it is necessary due to time not too long or it can be said is very short, the cost of the cheap route and do not need a bureaucracy to take a long message to the aspirations of the parties desired. The government also provides a better appreciation of the utilization of SMS as a medium in managing the aspirations of the community that can be used as one of the inputs and materials for the determination of policy considerations in the implementation of regional development